Computerized Tomography Technique for the Investigation of the Maxillary First Molar Mesiobuccal Root. (8th September 2013) - Corbella, Stefano; Del Fabbro, Massimo; Tsesis, Igor; Taschieri, Silvio
Abstract : The aim of this paper was to review the literature about the use of computerized tomography to evaluate the presence and characteristics of the second mesiobuccal canal in the maxillary first molar. An electronic search was performed. Frequencies of the presence of second mesiobuccal canal and root anatomy characteristics were extracted from the selected studies. Pooled frequencies were calculated as weighted means. Seven articles were included. A second mesiobuccal canal was present in 59.32% of the teeth, and it was noncommunicating in 58.45% of teeth presenting the canal itself. The most common root canal morphology was single canal or two separated canals. The present paper showed that cone beam CT is a viable radiologic device for the evaluation of the mesiobuccal root of maxillary first molars. In fact, it was observed that the frequency of second mesiobuccal canal detection is similar to those presented by clinical studies or micro-CT evaluations.